Enhancement of power system performance with wind farm disturbances - Mahmoud M. El-Sharkawy; Mahmoud A. Attia; Almoataz Y. Abdelaziz (Institute of Advanced Engineering and Science, 2019)
This paper discussed how wind farm disturbance, especially wind speed variability, can affect the performance of the power system. Also, it discussed how blades angels of wind turbine can be controlled to increase the energy efficacy of the power system. It showed that the optimized pitch angel controller using harmony search algorithm could enhance blades angels’ adjustments performance. First part, the paper explained the advantages of doubly fed induction generator in wind turbine system. Paper also enumerated the most probable ways to tame the wind speed variability challenge focusing on the pitch angle controller technique. After that, paper compared the system parameter`s result before optimization with values after optimized pitch angle controller gain (Kp). This comparison would be held in three cases, case of variable wind speed with normal operation condition, constant wind speed with line to ground fault condition and variable wind speed with line to ground fault condition. Finally, It demonstrated the MATLAB/SIMULINK model used illustrating results appeared and conclusion.